which expression is equivalent to ^3 square root 54x + 3^3 square root 2x if x does not equal 0?
![which expression is equivalent to 3 square root 54x 33 square root 2x if x does not equal 0 class=](https://us-static.z-dn.net/files/deb/2e0e941ff58bdbdbc22f3fb8f38d33a3.png)
You have the following expression:
³√54x + 3(³√2x), x ≠ 0
In order to simplify the previous expression, write 54x as 27(2x). Moreover, take into account that 27 = 3³ and ³√27(2x) = ³√(3³(2x)) = 3(³√2x). Then, you have:
³√54x + 3(³√2x)
= 3(³√2x) + 3(³√2x)
= 6(³√2x)
Hence, the equivalent expression is
A. 6(³√2x)